Critical Thinking Dispositions among Polytechnic Students: Why Does it Matter? - Shida, Nurul; Osman, Sharifah; Halim Abdullah, Abdul; Ismail, Norulhuda (International Journal of Engineering and Technology, 2018)
This study explored the critical thinking dispositions of polytechnic students. The study was conducted in the northern zone of Malaysia on 194 polytechnic students from the Departments of Mechanical and Electrical Engineering. Data were collected using the Engagement, Maturity, and Innovativeness (EMI) critical thinking disposition assessment. Then, the data was analysed using the SPSS version 21 software. Analysis of data comprised of descriptive statistics (percentage, mean and standard deviation) and inferential statistics (one-way analysis of variance, independent sample t-test, and Pearsonâ€™s correlation). The study points to no significant relation between gender and department. Further analysis showed that there is a strong relationship between CGPA and critical thinking disposition. Therefore, there is a need among students for special assistance in cultivating their critical thinking dispositions from the aspects of engagement and maturity.Â Â